Dampak Pengaruh Pengetahuan Zakat Dan Kepercayaan Karyawan Rumah Sakit Umum Daerah Bengkalis Terhadap Minat Membayar Zakat Penghasilan Dengan Lama Bekerja Sebagai Variabel Moderasi - Kiki Candri; Sri Rahmany; Muhammad Ashsubli; Zulfah Amalia (Jurnal Pajak dan Analisis Ekonomi Syariah, 2024)
This research aims to determine the impact of zakat knowledge and trust of Bengkalis regional general hospital employees on interest in paying zakat on income with length of work as a moderating variable..This type of research is quantitative research. The population in this study were Bengkalis Hospital employees who were ASN and Honorary totaling 284 people. The sample in this study were Bengkalis Hospital employees, totaling 166 people. Data collection techniques using a questionnaire. The data analysis technique used is descriptive statistical analysis and PLS (Partial Least Square) analysis. The results showed that knowledge of zakat had no effect on interest in paying professional zakat with an influence value of 0.12 and p-values of 0.889 (> 0.05). Trust has an effect on interest in paying professional zakat with an influence value of 0.615 and p-values of 0.000 (<0.05). Length of work has no significant effect on Interest in Paying Professional Zakat with an effect of -0.213 with p-values of 0.827 (>0.05). The length of work factor is not able to moderate the effect of zakat knowledge on interest in paying professional zakat with an effect of 0.078 with p-values of 0.488 (> 0.05). The length of work factor is not able to moderate the effect of trust on interest in paying professional zakat with an influence value of -0.065 with p-values of 0.524 (> 0.05).